Identification of Fingerprints Pattern in Mixed Family of Chinese-Javanese Ethnic - Nikmah, Istiftakhun; Fatchiyah, Fatchiyah (Journal of Tropical Life Science, 2017)
The aim of this study is to identify fingerprints patterns from the mixed family of Chinese-Javanese ethnic. The fingerprint patterns divided into three main patterns, i.e. arch, loop and whorl. The respondents were determined based on inclusion criteria (subject of research qualified as a sample) and the exclusion criteria (subjects which could not be used as a sample) through interviews and questionnaires. First, respondent’s fingers cleaned with alcohol or washed using soapy water. The patterns of fingerprint were taken by pressing one by one using an inked stamp pad. Then, printed on white paper which has been given a code and serial number of fingers for each respondent. The last step was to identify the specific characteristic of fingerprint patterns from the respondents and analyzed it while determining about similarity and variability of inter-generations. The results indicated that the mixed family of Chinese-Javanese ethnic had whorl variant pattern (plain whorl and double loop whorl) on the thumbs as a specific marker of Javanese ethnic. Otherwise, radial loop on the index and tented arch pattern on both index and little finger are the unique marker of Chinese ethnic. Thus, both Javanese and Chinese ethnic have co-dominant fingerprint patterns for mixed family of Chinese-Javanese ethnic.